Multiple Levels of Suffering: Discrimination in Health-Care Settings is Associated With Enhanced Laboratory Pain Sensitivity in Sickle Cell Disease. Issue 12 (December 2016) - Mathur, Vani A.; Kiley, Kasey B.; Haywood, Carlton; Bediako, Shawn M.; Lanzkron, Sophie; Carroll, C. Patrick; Buenaver, Luis F.; Pejsa, Megan; Edwards, Robert R.; Haythornthwaite, Jennifer A.; Campbell, Claudia M.
Abstract : Objective: People living with sickle cell disease (SCD) experience severe episodic and chronic pain and frequently report poor interpersonal treatment within health-care settings. In this particularly relevant context, we examined the relationship between perceived discrimination and both clinical and laboratory pain. Methods: Seventy-one individuals with SCD provided self-reports of experiences with discrimination in health-care settings and clinical pain severity, and completed a psychophysical pain testing battery in the laboratory. Results: Discrimination in health-care settings was correlated with greater clinical pain severity and enhanced sensitivity to multiple laboratory-induced pain measures, as well as stress, depression, and sleep. After controlling for relevant covariates, discrimination remained a significant predictor of mechanical temporal summation (a marker of central pain facilitation), but not clinical pain severity or suprathreshold heat pain response. Furthermore, a significant interaction between experience with discrimination and clinical pain severity was associated with mechanical temporal summation; increased experience with discrimination was associated with an increased correlation between clinical pain severity and temporal summation of pain. Discussion: Perceived discrimination within health-care settings was associated with pain facilitation. These findings suggest that discrimination may be related to increased central sensitization among SCD patients, and more broadly that health-care social environments may interact with pain pathophysiology.